2009
DOI: 10.3945/ajcn.2008.26919
|View full text |Cite
|
Sign up to set email alerts
|

Oral supplementation with probiotics in very-low-birth-weight preterm infants: a randomized, double-blind, placebo-controlled trial

Abstract: Supplementation with BB536-LGG may not improve the gastrointestinal tolerance to enteral feeding in very-low-birth-weight infants but may improve gastrointestinal tolerance in infants weighing >1000 g. This trial was registered at clinicaltrials.gov as NCT 00290576.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
127
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(147 citation statements)
references
References 32 publications
10
127
0
10
Order By: Relevance
“…Kitajima et al (34) found less gastric aspirates (Bifidobacterium breve), while Rougé et al (35) (mixture of Lactobacillus rhamnosus GG and Bifidobacterium longum) and Oncel et al (31) (L. reuteri) demonstrated reductions in time to full enteral feeds. We did not find any improvements in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Kitajima et al (34) found less gastric aspirates (Bifidobacterium breve), while Rougé et al (35) (mixture of Lactobacillus rhamnosus GG and Bifidobacterium longum) and Oncel et al (31) (L. reuteri) demonstrated reductions in time to full enteral feeds. We did not find any improvements in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The first studies on the gut bacterial colonization in preterm infants, based on culture methods and performed in the 80s, described a delayed colonization by many of the bacteria found in healthy fullterm infants [121][122][123]. However, more recent studies reported a greater delay either by culture [124][125][126] or cultureindependent methods [50,124,[126][127][128][129][130]. Recently, the use of a pyrosequencing-based method confirmed this aberrant pattern in low and very low birth weight infants [52].…”
Section: Gut Bacterial Establishment In Preterm Neonatesmentioning
confidence: 89%
“…On the other hand, other randomized trials have shown no difference in the time to attain full feeds between study and control infants 7,15 or of the volume of enteral feeds tolerated at 28 days after enrolment in the study 16 . Another randomized placebo-controlled trial has shown a decrease in "time to reach full feeds" in only infants with birth weight >1000 grams but not <1000 grams 17 .…”
Section: Discussionmentioning
confidence: 99%